2020
DOI: 10.3390/ijms21186970
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of miRNA Expression Profiles between HIV-1 and HIV-2 Infected Monocyte-Derived Macrophages (MDMs) and Peripheral Blood Mononuclear Cells (PBMCs)

Abstract: During the progression of HIV-1 infection, macrophage tropic HIV-1 that use the CCR5 co-receptor undergoes a change in co-receptor use to CXCR4 that is predominately T cell tropic. This change in co-receptor preference makes the virus able to infect T cells. HIV-2 is known to infect MDMs and T cells and is dual tropic. The aim of this study was to elucidate the differential expression profiles of host miRNAs and their role in cells infected with HIV-1/HIV-2. To achieve this goal, a comparative global miRNA exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 97 publications
(112 reference statements)
0
13
0
Order By: Relevance
“…Hypoxia directly influences viral proliferation, promoting or suppressing infectivity depending on the virus [ 57 ]. Similarly, Santanu et al 2020 also reported an alteration of the HIF-1 signaling pathway in the PBMCs of HIV-1 patients [ 28 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Hypoxia directly influences viral proliferation, promoting or suppressing infectivity depending on the virus [ 57 ]. Similarly, Santanu et al 2020 also reported an alteration of the HIF-1 signaling pathway in the PBMCs of HIV-1 patients [ 28 ].…”
Section: Discussionmentioning
confidence: 98%
“…Among these putative miRNAs, we highlight the miR-126-5p, hsa-miR-34a-5p and hsa-miR-148b-3p, whose expression levels were significantly higher in HIV/HCV coinfected PBMCs compared to HC. The miR-126-5p hepatic expression has been associated with HCV viral load [ 26 ], the circulating hsa-miR-34a-5p promotes liver fibrosis in CHC [ 27 ], and the hsa-miR-148b-3p has been previously identified as dysregulated in PBMCs of HIV patients [ 28 ]. Although these miRNAs were also associated with the regulation of carcinogenesis and antitumor responses [ 29 , 30 ], we found them involved in the PI3K-Akt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Other than antifungal host responses, miR-4755 and miR-4677 deregulation was previously linked to bacterial stimuli ( 58 , 66 ), miR-1305, miR-627, miR-543, and miR-581 to viral challenge, and miR-12135 to parasitic infections ( 67 ). miR-1277 and miR-365 were associated with host responses upon both bacterial and viral infections ( 68 72 ). Thus, although fewer miRNA species could be coupled with C. parapsilosis infections than with C. albicans , the majority of these were confirmed regulators of antimicrobial responses.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies determined the expression of cellular miRNAs in HIV-infected cell lines (Table 2 ). Recently, Biswas et al [ 118 ] established a comparative global miRNA expression profile in human PBMC and MDMs infected with HIV-1/HIV-2. Differentially expressed miRNAs were identified in these cells.…”
Section: Role Of Mirnas As Potential Biomarkers For Anal Cancer Screening In Plwhmentioning
confidence: 99%
“…Differentially expressed miRNAs were identified in these cells. Pathway analysis using Kyoto Encyclopedia of Genes and Genomes database showed that the deregulated miRNAs are likely to be involved in p53 signaling pathway, PI3K-Akt signaling pathways, Mitogen-activated protein kinase signaling pathways, FoxO signaling pathway, and NF-kappaB inhibitor signaling pathway, all of which play a role in carcinogenesis[ 118 , 119 ]. HIV Tat, Nef, and Vpr have been reported to alter the expression levels of many miRNAs and contribute to HIV pathogenesis (Table 3 ).…”
Section: Role Of Mirnas As Potential Biomarkers For Anal Cancer Screening In Plwhmentioning
confidence: 99%